Immunostimulatory Effect of Cayratia trifolia L. Domin on Granulocytes and Natural Killer Cells in Tuberculosis-Induced Rats - Wa Ode Salma; Mubarak Mubarak; Nasrudin Nasrudin; Parawansah Parawansah; Fadhliyah Malik; Asriullah Jabbar; Asniar Pascayantri; Esti Badia; Sernita Sernita; Nirwati Rusli; Lukman La Basy; Muhammad Ilyas Y (Tropical Biopharmaca Research Center, IPB University, 2026)
Pulmonary tuberculosis (TB) remains a major public health problem in Indonesia and a leading cause of death from infectious diseases, partly because of impaired host immunity. Galing (Cayratia trifolia L. Domin) has been reported to exert immunomodulatory effects in bacterial infections. This study evaluated the immunostimulatory effect of galing leaf and stem extracts on granulocytes and natural killer (NK) cells in a TB-induced rat model. Leaf and stem extracts were administered orally to 28 Wistar rats at doses of 400 and 500 mg/kg body weight for seven days, followed by induction with TB ESAT-6 antigen. Granulocyte counts were measured using a hematology analyzer, whereas NK cells were quantified by ELISA. Galing extract significantly increased granulocyte and NK cell expression compared with the negative control (p<0.05). These findings indicate that galing extract has potential as an immunostimulatory agent in pulmonary TB by enhancing granulocyte and NK cell responses.